The Research of Time Perception of Children with Hearing Impairments - Liliy Gatsoeva (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2018)
The article describes the peculiarities of perception of the length of time periods of children of elementary school age with hearing impairments. It is known that in the characteristics of time sensations the most important role is played by kinetic and auditory sensations. Therefore, the study of perception of time as an integral part of cognitive activity of children with hearing impairment is relevant. In studies whose purpose was to study the perception of the time of children with hearing impairment, we were asked to study the data of scientific sources and analyze the results of the pedagogical experiment. The purpose and tasks were realized by methods of analysis and generalization of scientific and methodological literature and pedagogical experiment. In investigational participated 24 children (an experimental group consisted of 12 girls with violation of rumor, control – from 12 girls in that a rumor was in a norm). For the study of perception of time in our research we used methodology of measuring of minute interval lot and executing an ccount to 60 after a second. According to the results of the experiment, it was found that the majority of girls who participated in the study demonstrated a decrease in the length of the individual minute. There was no significant difference between the mean group values of the control and experimental groups in the first and second tests (p> 0,05). The analysis of the results showed an ambiguous picture, which can be related to external and internal factors and features of the subjects. Conclusions. Perception of time is an important characteristic of the mental activity of a child with hearing impairment. It determines the level of orientation of such a child in the world around him and depends on both external factors and the characteristics inherent in the child. It is natural to assume that such an individual characteristic as the perception of time can depend on the nature of the child, the degree and timing of hearing loss, the level of knowledge, the emotional state, and will be the subject of our further research.